Strategi Pengembangan Wisata Pantai Ponnori di Kecamatan Larompong Selatan Kabupaten Luwu - Erwin Asjayasari Arsyad; Amal Arfan; Uca Sideng (Universitas Negeri Makassar, 2020)
This study aims to determine: 1) Beach typology conditions for the development of ponnori beach tourism in Larompong Selatan District Luwu District. 2) Strategy of ponnori beach tourism development in Larompong Selatan Sub-district Luwu Regency. Data collection such as: Observation, Interview and Documentation. The analysis technique used is qualitative descriptive analysis and swot analysis. The results showed: The physical condition of Ponnori Beach is the highest peak of 240 cm and the lowest retrograde is 90 cm with an average tidal range of 166,08 cm. Average wave heights range from 0.04 m - 0.18 m with an average of 0.08 m, and a mean current velocity of 0.05 m / s. The depth of Ponnori Beach waters 0-2 m with 100% waters brightness and water temperature 28-29ºC. The slope of the slope is in the flat category with a value of 1-2 degrees. So that the value of Ponnori Beach's physical parameter feasibility is 95,88% is in the range of 80 - 100% which fall into the very feasible category (S). The social condition of Ponnori Beach is the lack of facilities and infrastructure due to budget constraints and the lack of promotion efforts and the ponnori beach development program is still simple and the lack of professional workforce in the management of ponnori beach tourism. And the eligibility value for Ponnori Beach social parameter is categorized as feasible with a feasibility score of 57.14%. From the SWOT analysis conducted Ponnori Beach Tour is included in the First Quadrant on the SWOT diagram is the Aggressive Strategy, where the situation can be done by utilizing the strength and opportunities in order to increase the growth of Ponnori Beach Tour. To realize Ponnori Beach as a coastal tourist attraction that attracted many people it is necessary cooperation between the government and local communities as well as private investors in the development of ponnori beach tourism.